Pembelajaran Group Investigation dan Talking Chips untuk Meningkatkan Aktivitas dan Hasil Belajar - Moh. Farid Anwar; Kardiana Metha Rozhana (Jurnal Bidang Pendidikan Dasar, 2020)
Abstract: Conventional learning models are less effective for use in the 2013 curriculum which emphasizes scientific approaches. Innovative learning models are needed for learning in the 2013 curriculum. One form of innovative learning models is the GI learning model. The purpose of the research is to describe the application of GI learning models and Talking Chips methods to improve student learning outcomes and activities. This type of research is used by CAR, with four steps including planning, treatment and observation, reflection. While the techniques for obtaining data through observation, tests, interviews, and documentation. Learning outcomes cycle 1 gained a score of 84 to 89 and cycle 2 a score of 92 to 96. Abstrak: Model pembelajaran konvensional kurang efektif untuk digunakan pada kurikulum 2013 yang menekankan pada pendekatan scientific. Model pembelajaran inovatif diperlukan untuk pembelajaran pada kurikulum 2013. Salah satu bentuk model pembelajaran inovatif adalah model pembelajaran GI. Tujuan penelitian yaitu mendeskripsikan penerapan model pembelajaran GI dan metode Talking Chips untuk meningkatkan hasil dan aktivitas belajar siswa. Jenis penelitian yang digunakan PTK, dengan empat langkah diantaranya planning, treatment and observation, reflection. Sedangkan teknik untuk memperoleh data melalui observasi, tes, wawancara, serta dokumentasi. Hasil belajar siklus 1 memperoleh skor 84 menjadi 89 serta siklus 2 skor 92 menjadi 96.